Peran Komunitas Online Dalam Membangun Preferensi Merek Otomotif Jepang (Studi Netnografi Pada Grup Facebook Motuba) - Amartha, Handhika Trian; Hariyanto, Fajar; Ramdhani, Muhammad (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
The purpose of this research is to determine the role of online communities in building preferences for Japanese automotive brands (netnographic study of the Motuba Facebook group) (student study at the Faculty of Social and Political Sciences, Singaperbangsa University, Karawang). Japanese popular culture, or what is often called J-pop culture, is a global phenomenon that attracts the attention of many people in various countries, including Indonesia. The qualitative research design used in this study is a netnographic study. This approach allows researchers to understand and analyze interactions, behavior and community dynamics in depth through participant observation in online environments. An interview with Mbah Mikael Bekti revealed that the Motuba group is a relatively new community for him, but members tend to have a preference for Japanese automotive brands due to personal experience and affordable prices. Communication within the group occurs directly through the comments feature, with little use of special terms or symbols.